2005
DOI: 10.1111/j.1468-1331.2005.01330.x
|View full text |Cite
|
Sign up to set email alerts
|

EFNS guidelines on cognitive rehabilitation: report of an EFNS task force

Abstract: Disorders of language, spatial perception, attention, memory, calculation and praxis are a frequent consequence of acquired brain damage [in particular, stroke and traumatic brain injury (TBI)] and a major determinant of disability. The rehabilitation of aphasia and, more recently, of other cognitive disorders is an important area of neurological rehabilitation. We report here a review of the available evidence about effectiveness of cognitive rehabilitation. Given the limited number and generally low quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
55
0
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(64 citation statements)
references
References 137 publications
(143 reference statements)
3
55
0
6
Order By: Relevance
“…On the other hand, Redick et al (2013) and Dunning, Holmes, and Gathercole (2013), found no transfer effects of working memory training on tests of other cognitive functions. Treatment of attention deficits in order to increase memory performance after organic brain damage has been investigated, partly with positive (Cappa et al, 2005;Malia et al, 2004;Gauggel & Niemann, 1996), and partly with negative results (Hildebrandt, BussmannMork, & Schwendemann, 2006;Spahn et al, 2010). The results of this study are in line with studies reporting negative findings.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…On the other hand, Redick et al (2013) and Dunning, Holmes, and Gathercole (2013), found no transfer effects of working memory training on tests of other cognitive functions. Treatment of attention deficits in order to increase memory performance after organic brain damage has been investigated, partly with positive (Cappa et al, 2005;Malia et al, 2004;Gauggel & Niemann, 1996), and partly with negative results (Hildebrandt, BussmannMork, & Schwendemann, 2006;Spahn et al, 2010). The results of this study are in line with studies reporting negative findings.…”
Section: Discussionsupporting
confidence: 92%
“…The search for generalization effects of cognitive improvement traditionally relies on interventional studies, treating, for instance, attention in order to also induce improvement in memory (Cappa et al, 2005;Gauggel & Niemann, 1996;Malia et al, 2004;Spahn et al, 2010). Other methods to look for factors implicated in recovery are regression analyses and/or other multivariate statistical tests.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Cognitive rehabilitation focuses on restoring impaired function via repeated skills practice and facilitating compensation for deficits through instruction in cognitive strategies (Kesler et al, 2011). Cognitive rehabilitation has been well-studied as an intervention following traumatic brain injury or stroke, with sufficient evidence to support its use as a therapeutic too (Cicerone et al, 2000; Cappa et al, 2005). However, the study of cognitive rehabilitation in epilepsy has been limited, especially in children, and clinically only 23% of children with CAE receive any kind of intervention to help with their school struggles (Caplan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic activities include those similarly used in cognitive rehabilitation (Cappa et al, 2005;Helmick, 2010), such as process, strategy and functional training activities, errorless learning, and awareness training (Golisz, 2009;Malia et al, 2004;Ueno et al, 2009). Other goals include increasing tactile sensitivity and other visual-spatial, tactilekinesthetic, and fine motor skills.…”
Section: An Overview Of Cpmmentioning
confidence: 99%